Arabic Language Pragmatics In Lombok Indonesia: Arabization Systems And Contestation In Cultural Construction - Satriawan, Satriawan (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study tries to explore the use of Arabic in Lombok, West Nusa Tenggara-Indonesia which is influenced by the Arabization system through contestation and cultural channels that have an impact on the daily communication of several Muslim groups in Lombok. This research uses qualitative methods with a field study approach and literature review in discussing Arabic pragmatics in Lombok Indonesia between the Arabization system and contestation in cultural construction. The theory used is socio-linguistic from John J. Gumperz related to the communicative context. The question of this paper is how did the Arabization system affect the use of Arabic in Lombok? What impact does it have on the use of Arabic in the daily context and social interaction of the people of Lombok? How does the cultural construction of Arabic language use affect relations between individuals and groups in Lombok? The results of this study reveal the Arabization system in Lombok can be seen from the use of Arabic vocabulary in daily conversation, writing the names of places, and individuals, to the context of religious and educational rituals. The effects on the use of Arabic in the daily context and social interaction of Lombok people are the neglect of local languages, social misunderstandings, educational inequality, foreign cultural influences, dependence on religious literature, social exclusivity, and difficulties of national integration. While the cultural construction of the use of Arabic by Wahhabi groups in Lombok is not only a means of communication, but also a cultural and ideological instrument that strengthens group identity, supports education and dissemination of teachings, and strengthens connectivity with the global Muslim community. On the other hand, the use of Arabic by Salafi, Wahhabi groups in Lombok strengthens their religious identity and affirms their commitment to a purer and textual understanding of Islam.